Parameteric thermal process models of friction stir welding - Uslu, Mehmet Yildirim (My University, 2017)
The Friction Stir Welding process is a rotating tool, that consists of a specialy designed shoulder and pin, that is plunged into the joining line of the required material and traverses along this line. The friction is induced by the rotating tool causes the workpiece material to rise to an operating temperature of 70% to 90% of the workpiece material's melting temperature and resulting in, no phase change, nor any defects associated with phase change, occurs in the workpiece. The increased temperature of the material causes the shear yield strength to drastically decrease thus allowing the two pieces to plasticise, easily stir around the tool and subsequently join. As the tool traverses along the workpiece, the softened material cools in the wake of the rotating tool and recrystallises, forming a ne grained microstructure. Attempts to develop an innovative tool to correlate the resulting of thermal models with process parameters are scarce. In this work, 6056-T4 and 6082-T6 Aluminum alloy sheets are friction stir welding at different rotational and translational speeds during the experimental aspect and material 2024-T3 for the analytical calculations. The effects of process parameters on the resulting thermal and mechanical properties are investigated. The results show that the use of coolant during the friction stir weld decrease heat generation substantially, this can also affect the force of the weld. It is also observed that the shear strenght of the processed sheet depends strongly on the rotational and translational speeds as weld as the thermal aspect and varies widely within the processed region, this was shown in this study by evaluating the thermal aspects of different weld types namely the Standard tool, Bobbin tool and the innovative tool. In addition. The proposed approach involves determination of the use of the friction stir welding in different thermal conditions and championing the use of an innovative tool.
A Dissertation for the Master’s Degree in Mechanical Engineering School of Mechanical, Industrial & Aeronautical Engineering Date: 02/02/2017
Keywords: Friction stir welding; Friction welding; Heat--Transmission